Theory of Nova Outbursts and Type Ia Supernovae - M. Kato; I. Hachisu (Acta Polytechnica CTU Proceedings, 2015)
We briefly review the current theoretical understanding of the light curves of novae. These curves exhibit a homologous nature, dubbed the universal decline law, and when time-normalized, they almost follow a single curve independently of the white dwarf (WD) mass or chemical composition of the envelope. The optical and near-infrared light curves of novae are reproduced mainly by free-free emission from their optically thick winds. We can estimate the WD mass from multiwavelength observations because the optical, UV, and soft X-ray light curves evolve differently and we can easily resolve the degeneracy of the optical light curves. Recurrent novae and classical novae are a testbed of type Ia supernova scenarios. In the orbital period versus secondary mass diagram, recurrent novae are located in different regions from classical novae and the positions of recurrent novae are consistent with the single degenerate scenario.